Talent management activities of disability training and placement agencies in India - Kulkarni, Mukta; Scullion, Hugh (International journal of human resource management, 2015)
This study seeks to outline activities of training and placement agencies in India aimed at employment of persons with a disability. We contend that persons with a disability are an underutilized human resource and that utilizing their abilities should be a key part of an inclusive approach to talent management. As there is little empirical research on this subject, our approach is exploratory and we seek to create a platform for further studies. A key finding of the study is the preference of agencies to engage in non-traditional and ad hoc approaches to build and showcase underutilized talent of those with a disability. Based on present findings and the contextual approach to talent management, a more comprehensive agenda for future research areas in inclusive talent management is outlined.